Em-ka-ce: 30 let javnega zavoda Mladinski kulturni center Maribor (University of Maribor Press, 2023)
Em-kah-tseh: 30 Years of the Youth Cultural Centre Maribor Public Institution. The public institution Youth Cultural Centre Maribor, also known as MKC (em-kah-tseh), constitutes an integral part of the developmental history of multiple generations of young individuals in Maribor. In the 1960s, the Youth Club at Orožnova 2 commenced its operations, hosting a myriad of activities for young people over the subsequent two decades. In 1988, the club underwent a name change to MKC Club, and in 1993, the MKC Maribor public institution was officially established. This publication provides a concise and transparent presentation of the institution’s rich history within the realms of youth culture and politics, accompanied by visual material. In addition to showcasing diverse programs and projects, encompassing musical, literary, and multidisciplinary artistic creations, as well as gallery and festival activities, support for marginalized social groups, and youth tourism, it incorporates historical documents and media reports associated with the institute’s operations. Furthermore, it includes a presentation of the institute’s publishing production. All of these elements bear witness to the institution’s vital role in actively engaging young people in the cultural and social life of the city.